The Effectiveness of Using Continuous Variable Transmission (CVT) in 2WD Buggy Vehicles - I Putu Darmawa; I Made Anom Adiaksa; Ida Bagus Puspa Indra; I Wayan Suma Wibawa (Universitas Negeri Padang, 2023)
Continuous Variable Transmission (CVT) is a transmission system that does not have gears like in manual transmission cars or conventional automatic transmission cars. CVT has the advantage of being able to maintain the proper rotational speed at any time in terms of engine efficiency by changing the speed ratio flexibly and continuously. A continuously variable transmission (CVT) is a transmission that can change steplessly through an infinite effective gear ratio between maximum and minimum. This is in contrast to other mechanical transmissions which only allow a few different gear ratios to choose. The flexibility of the CVT allows the drive shaft to maintain a constant angular speed over the output speed range. Torque is transmitted from the drive to the pulley which is driven by friction acting between the belt and pulley surfaces. Tests were carried out using a dynotest to obtain wheel rotation data and the resulting torque. The loading is given from 3 kg, 5 kg, 7 kg and 8 kg, the engine rpm used is 5500 rpm, 6000 rpm, 6500 rpm, 7000 rpm and 8000 rpm. Rear wheel rotation is inversely proportional to the load, the greater the load the rotation will decrease. Load is directly proportional to torque, the greater the load given the torque will increase. The CVT system is still effective for use as a power successor. The power that can be transmitted is still greater than 50%, namely 68%.